1968
DOI: 10.1002/1097-0142(196807)22:1<173::aid-cncr2820220121>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Coincident basophilic chronic myelogenous leukemia and pulmonary tuberculosis. Associated with extreme elevations of blood histamine levels and maturity onset asthma

Abstract: A case of coincident basophilic chronic myelogenous leukemia and pulmonary tuberculosis is reported. Marked elevations in serum histamine levels were associated with maturity onset‐bronchial asthma which was controlled with antihistamine medication. The diagnosis of tuberculosis was established by pleural fluid cultures. The diagnosis of chronic myelogenous leukemia was established by determination of leukocyte alkaline phosphatase levels and chromosome studies. The importance of such studies in cases of tuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…7 But without such a treatment, occurrence of TB in patient with CML is an uncommon entity and rare cases were reported. [12][13][14] Silva et al in a large retrospective study found only one case of TB among 45 CML cases. 11 In our patient, peritoneal TB was diagnosed first and haematological parameters initially gave us an impression of leukamoid reaction, but the initial bone marrow examination failed to identify any granuloma, AFB or malignancy and subsequently, within the next two weeks the typical picture of CML became obvious.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…7 But without such a treatment, occurrence of TB in patient with CML is an uncommon entity and rare cases were reported. [12][13][14] Silva et al in a large retrospective study found only one case of TB among 45 CML cases. 11 In our patient, peritoneal TB was diagnosed first and haematological parameters initially gave us an impression of leukamoid reaction, but the initial bone marrow examination failed to identify any granuloma, AFB or malignancy and subsequently, within the next two weeks the typical picture of CML became obvious.…”
Section: Discussionmentioning
confidence: 98%
“…[3][4][5][6][7] TB can complicate acute leukaemias and lymphomas, but concomitant diagnosis of TB and CML is an uncommon entity. [8][9][10][11][12][13][14] Case report A 52-year-old diabetic lady presented with one month history of low grade, intermittent fever and gradual abdominal distension for two weeks. She did not have any cough, haemoptysis, night sweats, jaundice, leg swelling, chest pain, palpitation, joint pain or weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…However, a higher dose increases the risk of drug side effects, which can reduce patient adherence. The relationship between CML and TB has been reported in only anecdotal case observations . The largest CML case series published to date reports the cases of only three patients who developed active TB after a median of 17 months of imatinib therapy .…”
mentioning
confidence: 99%